2007
DOI: 10.1002/qj.38
|View full text |Cite
|
Sign up to set email alerts
|

Role of the quasi‐biweekly oscillation in the onset of convection over the Indochina Peninsula

Abstract: ABSTRACT:The characteristics of convection onset over the Indochina Peninsula and its possible mechanism are investigated using the reanalysis of the National Centers for Environmental Prediction/National Center for Atmospheric Research (NCEP/NCAR) and the black-body temperature at the top of the cloud (T BB ). Results show that the convection onset occurs before the systemic northward progression of the tropical convection and is earlier than the onset of the summer monsoon over this region. The prominent dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The study of the QBWO in boreal spring is useful because it may significantly impact the Asian monsoon onset (Zhang et al 2002;Wen and Zhang 2007). The generation mechanism for QBWO in boreal spring might be different from that in other seasons.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the QBWO in boreal spring is useful because it may significantly impact the Asian monsoon onset (Zhang et al 2002;Wen and Zhang 2007). The generation mechanism for QBWO in boreal spring might be different from that in other seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Intraseasonal oscillation is one of the most important components of the tropical atmospheric variation. It generally involves two major modes: the well‐known Madden‐Julian Oscillation (MJO) with a characteristic period of 30–60 days [ Madden and Julian , , ] and the quasi‐biweekly oscillation (QBWO) with a typical time band of 10–20 days [ Krishnamurti and Ardanuy , ; Chen and Chen , , ; Fukutomi and Yasunari , , ; Wen and Zhang , , ; Jiang and Lau , ; Kikuchi and Wang , ; Wen et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Observational facts of MJO have been documented by abundant studies [e.g., Li and Wu , ; Li and Zhou , ; Salby and Hendon , ; Jones and Weare , ; Maloney and Hartmann , ; Woolnough et al ., ; Fu et al ., ; Sperber , ; Jiang et al ., , ; Zhang , ; Li et al ., ] and many investigations have been conducted on its impacts on global weather and climate [ Higgins and Shi , ; Lawrence and Webster , ; Wheeler and McBride , ; Donald et al ., ; Jeong et al ., ; Wheeler et al ., ; Zhang et al ., ; Tong et al ., ; Jia et al ., ; Li et al ., ]. Compared to the MJO, less effort has been devoted to understanding the QBWO, and most previous studies of QBWO have focused on the tropical Asian monsoon region and the western North Pacific (WNP) including the South China Sea (SCS) [ Krishnamurti and Ardanuy , ; Chen and Chen , , ; Fukutomi and Yasunari , , ; Chen et al ., ; Chan et al ., ; Mao and Chan , ; Zhou and Chan , ; Wen and Zhang , ; Chen and Sui , ; Park et al ., ]. Atmospheric oscillation of 10–20 days was earliest reported in the Indian monsoon [ Krishnamurti and Ardanuy , ; Chen and Chen , ].…”
Section: Introductionmentioning
confidence: 99%
“…The commencement of convection, however, occurred in April before monsoon onset. Wen and Zhang (2007) suggested that premonsoon precipitation and monsoon onset are associated with different background circulations and mechanisms. The premonsoon convection may be triggered by the tropical quasi-biweekly oscillation propagating from the south and cold surges invading from the north.…”
Section: Distribution Of Monsoon Precipitation and Wind-terrain Intermentioning
confidence: 98%